The Influence of Competitive Advantage and Product Innovation on Marketing Performance on Tegalan Batik Business in Tegal Regency - Niken Wahyu C. (Jurnal Akuntansi, Manajemen dan Ekonomi, 2017)
This study aims to examine the influence of competitive advantage and product innovation on marketing performance on batik business in Tegal regency and which variable is the greater the effect. The hypothesis to be tested is to analyze empirically the influence of competitive advantage and product innovation on marketing performance on batik tegalan business in Tegal regency. The sample in this research was all tegalan batik craftsmen in Bengle village of Tegal regency. Total population to be samples was 85 tegalan batik craftsmen. Data analysis used Spearman rank correlation formula and multiple linear regression. The result of statistical test showed that partially product innovation has a positive effect on marketing performance equal to 67.7% and competitive advantage has positive effectono marketing performance equal to 68.5%. Then the test result simultaneously indicated that product innovation and competitive advantage variables have influence of 77.7% on marketing performance. However, the variable of competitive advantage was the most influencer on marketing performance equal to 68.5%. Result of coefficient determination test showed the amount of marketing performance that can be explained by the variable of product innovation and competitive advantage of 60.4% and the remaining as much as 39.4% was influenced by other unexplainable factors.